Analisis Gangguan Ekspresi Verbal Tokoh Amandus: Penyakit Alzheimer dalam Film Honig im Kopf (Kajian Psikolinguistik) - Miftahul Ilmi; Jufri Jufri; Hasmawati Hasmawati (Phonologie : Journal of Language and Literature, 2021)
Abstract. This study aims to analyze and describe the forms of verbal expression disorders in the form of problematic utterances of the character Amandus in the film Honig im Kopf. For this purpose, the researcher used a qualitative descriptive type of research. Data were analyzed from two sources, namely primary data sources in the form of utterances of the character Amandus from the film Honig im Kopf and secondary data sources in the form of scientific journals, articles and psycholinguistic books relevant to the research topic raised. Collecting data using the technique of listening and noting. The results of the data collection were then analyzed using the Miles & Huberman interactive analysis model. Furthermore, the data analysis results into the forms of symptoms of verbal expression disorders due to Alzheimer's disease based on the theory of Klimova & Kuca (2016) and the forms of symptoms based on the theory of Chaer (2015). From the results of the study, it was found that there were 32 data that met the symptoms of Alzheimer's disease according to the theory of Klimova and Kuca (2016) and were divided into four forms. Furthermore, it was found as many as 32 data that overcome the symptoms of Alzheimer's disease Chaer (2015) theory and divided into three forms. Then it can be said that there are 64 data that are divided into two theories of Alzheimer's disease, namely with impaired verbal expression of the character Amandus.